2018
DOI: 10.1177/0004867418767315
|View full text |Cite
|
Sign up to set email alerts
|

A decision support tool to inform local suicide prevention activity in Greater Western Sydney (Australia)

Abstract: This study demonstrates the utility of dynamic simulation models, co-designed with multi-disciplinary stakeholder groups, to capture and analyse complex mental health and suicide prevention regional planning problems. The model can be used by WentWest - Western Sydney Primary Health Network as a decision support tool to guide the commissioning of future service activity, and more efficiently frame the monitoring and evaluation of interventions as they are implemented in Western Sydney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…The variation in responses is not surprising given the paradigm shift that systems thinking represents, and the perceived lack of robust examples of systems approaches being applied to policy which undermines its value proposition (although we note there are examples, eg, 11,14,27,34,59,[82][83][84][85] ). People make sense of the world given what they know so, without a compelling rationale, we tend to hold on to established mental models and avoid the disruption of seeing the world in radical new ways.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in responses is not surprising given the paradigm shift that systems thinking represents, and the perceived lack of robust examples of systems approaches being applied to policy which undermines its value proposition (although we note there are examples, eg, 11,14,27,34,59,[82][83][84][85] ). People make sense of the world given what they know so, without a compelling rationale, we tend to hold on to established mental models and avoid the disruption of seeing the world in radical new ways.…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of our model would provide an opportunity for interservice cooperation and higher quality care for young people. The application of innovative data‐driven approaches, such as dynamic systems modelling (a computer simulation approach that can be used to test likely impacts on the health system of different intervention combinations over the short and long term), has recently created new insights into complex patient flows and can highlight gaps in service provision within locally connected care systems rather than within a single service . These insights can identify service gaps and assist in building robust connections between previously separate and closed systems, to ensure that mental health services address the complete spectrum of needs for young people over time.…”
Section: Creating Locally Connected Care Systemsmentioning
confidence: 99%
“…For example, subsequent hospital admission rates have been shown to be higher among those who did not attend their first appointment for psychiatric outpatient treatment following referral from a primary care setting, 2 and a recent study indicated that interventions to re-engage those lost to mental health services had the greatest potential impact on reducing the incidence of suicide. 3 In addition, treatment non-attendance is also associated with additional work load and administrative burden in following-up patients and managing service attendance, 4 potentially decreasing the expected cost-effectiveness of services.…”
Section: Introductionmentioning
confidence: 99%